PENGARUH PENATAUSAHAAN BARANG MILIK NEGARA DAN PENERAPAN SISTEM INFORMASI MANAJEMEN AKUNTANSI BARANG MILIK NEGARA (SIMAK BMN) TERHADAP KUALITAS LAPORAN KEUANGAN (STUDI EMPIRIS PADA KANTOR KEMENTRIAN NEGARA/LEMBAGA WILAYAH ACEH) - Fajri, Abdul Malik; Fuadi, Raida (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
The purpose of this research is to examine the effect of administration of state property and application of SIMAK BMN on the quality of financial reports. The population of this research is all offices within the ministries and institutions in the Aceh region which the sampling technique uses non probability sampling with census method. Respondents who are the object of this research are those who are most responsible for BMN, consisting of goods managers / users and SIMAK BMN application operators, so that 68 respondents are obtained. Data analysis method used is multiple linear regression with the help of SPSS 25. The result of this research shows that (1) administration of state property and the application of SIMAK BMN has a positive effect on the quality of financial reports, (2) partially administration of state property has a positive effect on the quality of financial reports and (3) partially application of SIMAK BMN has a positive effect on the quality of financial reports